Empirical Analysis of Policy Lapse Behavior Among Life Insurance Customers at PT Prudential Binjai - Siregar, Aspan Sofyan; Imsar, Imsar; Atika, Atika (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the factors that influence the lapse of life insurance policies on customers of PT Prudential Insurance Binjai Branch. Lapse is the termination of an insurance policy due to the customer's inability to pay premiums after the grace period, which is a big challenge for the insurance industry. The research method used is a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The results showed that the main factors causing policy lapse were unstable economic conditions, lack of insurance literacy, changes in personal financial needs, and social and cultural influences. Some customers experienced a decrease in income due to job changes or family conditions, so they decided not to continue paying premiums. In addition, a lack of understanding of the long-term benefits of insurance makes customers more vulnerable to lapse decisions. The impact of policy lapse is significant for the company, including loss of premium income, reduced customer retention rates, and potential damage to the company's reputation. Although lapse can reduce claim payment obligations for the company, the negative impact on cash flow is often greater. This research provides insights for insurance companies in designing strategies to reduce lapse rates. Some recommendations that can be implemented include increasing insurance education to customers, offering more flexible products according to customer financial needs, and strengthening communication and relationships with customers to remain committed to paying premiums. With a more proactive approach, companies can increase customer satisfaction and loyalty and ensure business sustainability in the midst of intense insurance industry competition.